2017
DOI: 10.1017/s0261444817000295
|View full text |Cite
|
Sign up to set email alerts
|

Going covert: Inner and private speech in language learning

Abstract: Roughly 30 years ago researchers in the second language acquisition (SLA) field started to take a focused interest in the study of inner speech (IS) and private speech (PS) processes in second language (L2) learning and use. The purpose of this review is to assess the status of current research and the progress made during the last ten years on the development and experience of covertly using a language other than the first. The review begins with a critical discussion of the challenges involved in defining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 104 publications
(202 reference statements)
1
12
1
Order By: Relevance
“…degree of daily use or confidence in using a language). Also, given the fact that the class discussion in the present study was mainly content-based rather than language oriented, most of the instances of PS reported were not directly related to linguistic or metalinguistic issues, including translating the text or vocabulary or grammar practice (Guerrero, 2018). The functions of PS in the current study categorically differed from the functions highlighted in previous research.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…degree of daily use or confidence in using a language). Also, given the fact that the class discussion in the present study was mainly content-based rather than language oriented, most of the instances of PS reported were not directly related to linguistic or metalinguistic issues, including translating the text or vocabulary or grammar practice (Guerrero, 2018). The functions of PS in the current study categorically differed from the functions highlighted in previous research.…”
Section: Discussioncontrasting
confidence: 68%
“…For instance, research has shown that MT helps learners to understand instructions and explain content; facilitates comprehension and production of SL/FL; and, promotes collaborative talk (Guerrero, 2018;Ma, 2016). For instance, Varshney and Rolin-Lanziti's (2006) study investigating the functions of MT of the first year students learning L2 (i.e.…”
Section: Functions Of Mt In Efl Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered to be an important cognitive resource that “regulate[s] the mental activity of the individual in the execution of a cognitive or physical task” (Lantolf & Thorne, 2006, p. 76). Findings have shown that individuals use private speech to mediate their learning; they use it while problem solving, memorizing, or internalizing a difficult concept, with its use becoming more frequent as the cognitive demands of the task increase (e.g., de Guerrero, 2018; Jiménez‐Jimenéz, 2015; McCafferty, 1992; see Swain & Watanabe, 2013, on the related concept of languaging ).…”
Section: Self‐talkmentioning
confidence: 99%
“…Wang and Shih 35 (2011) used a self-report method, whereby participants were prompted to focus on and analyze their inner speech; however, as a measurement tool, self-report has a certain subjectivity. Despite the obvious limitations of self-report methods, Guerrero (2018) suggests that self-questionnaires and introspective verbalization of thinking might still provide useful insights regarding language learning and production, especially when combined with other research strategies that are focused on the participants' personal opinion and perception.…”
Section: English As the Predominant Language For Communication And Thmentioning
confidence: 99%